2020
DOI: 10.21203/rs.3.rs-28768/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Umbilical cord-derived mesenchymal stromal cells immunomodulate and restore actin dynamics and phagocytosis of LPS-activated microglia via PI3K/Akt/Rho GTPase pathway

Abstract: Background: Microglia are the immune cells in the central nervous system constantly surveying their environment and reacting to various injuries. Activated microglia may cause impaired synaptic plasticity, therefore modulating and restoring them to more neutral phenotype is crucial to counteract a pro-inflammatory, neurotoxic state. In this study, we focused on elucidating whether human umbilical cord (UC) tissue-derived mesenchymal stromal cells (MSCs) can exert immunomodulatory effect and change the phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Morphological and phagocytotic analyses revealed that lipopolysaccharide stimulation significantly changed microglial morphology to amoeboid in which F-actin spread with ruffle formation resulting in reduced phagocytosis of Escherichia coli , while MSC co-culture induced shrinkage and concentration of F-actin to form an actin ring, thereby restoring phagocytosis. 44 These effects of UC-MSCs that modulate the activated microglia may be a therapeutic potential for the treatment of neurological disorders accompanied by inflammation.…”
Section: How Th and Cell Therapy Prevent Newborn Brain Damage From Hie?mentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological and phagocytotic analyses revealed that lipopolysaccharide stimulation significantly changed microglial morphology to amoeboid in which F-actin spread with ruffle formation resulting in reduced phagocytosis of Escherichia coli , while MSC co-culture induced shrinkage and concentration of F-actin to form an actin ring, thereby restoring phagocytosis. 44 These effects of UC-MSCs that modulate the activated microglia may be a therapeutic potential for the treatment of neurological disorders accompanied by inflammation.…”
Section: How Th and Cell Therapy Prevent Newborn Brain Damage From Hie?mentioning
confidence: 99%
“…MSCs are reported to protect brains against global and local neuroinflammatory cascades triggered by HI events. 39 44 However, at times MSCs have both anti- and proinflammatory effects. Indeed, in our study, some UC-MSCs caused inflammatory response in resting-surveying (not activated) microglia, indicating that MSCs should not be administered to healthy brain with no inflammation.…”
Section: How Th and Cell Therapy Prevent Newborn Brain Damage From Hie?mentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated that secretomes from MSCs can change the phenotype of activated microglia. Umbilical cord derived MSCs immunomodulated microglia and changed the phenotype of LPS-activated microglia restoring actin dynamics and phagocytosis by increasing active Rho GTPase, in which microglia changed their amoeboid to a more ramified pattern (Mukai et al, 2021). This suppression and immunomodulation of activated microglia by MSCs may lead to therapeutic potential for individuals with ASD in which excessive microglial activation lead to aberrant neural connections.…”
Section: Ucbs For Individuals With Asdmentioning
confidence: 96%